Food and power in Hawaiʻi : visions of food democracy - Kimura, Aya Hirata, 1974-; Suryanata, Krisnawati (Food in Asia and the Pacific., 2016)
What are the challenges to the food system in Hawai'i? Food and Power in Hawai'i explores issues facing the way we eat and produce (or do not produce) food in Hawai'i. Given its island geography, high dependence on imported food has been portrayed as the primary problem, and localization has been proposed as the dominant solution in Hawai'i. But the book argues that much more is needed to transform the food system into one that is just, equitable, secure, and healthy. The book points out the diversity of the challenges Hawai'i faces-energy-intensive farming; gendered and racialized farming populations; controversies over the ownership, costs, and benefits of biotechnology; high food insecurity for marginalized communities; and stratified access to nutritious foods. Defying the reductive approach that looks only at calories or tonnage of food produced and/or consumed in the state as the indicator of the soundness of the food system, the book points out how the food problems are necessarily layered with other sociocultural and economic problems and uses food democracy as the guiding framework. "Food and Power in Hawai'i" explores various issues, including agriculture, land use, colonialism, biotechnology, agricultural tourism, and farmers' markets; and explains how these issues relate to movements toward food democracy